Integration of Gamification in Physics Learning: A Development Study of FISIPOLY Using the Genially Platform for 10th Grade High School Students - Fadhila Ramadhani; Daru Wahyuningsih (Universitas Sebelas Maret, 2025)
Physics is often perceived as a challenging subject due to its abstract nature and reliance on advanced mathematical skills, leading to students’ difficulties in grasping core concepts. Gamification in education has been proven to enhance motivation and engagement in learning. This study aims to develop a Genially-based learning media, FISIPOLY, focused on Global Warming for 10th-grade senior high school students. The research employed the 4D model (Define, Design, Develop, Disseminate). Validation was conducted by material and media experts, followed by product trials involving 10th-grade students. Results demonstrated that FISIPOLY met valid criteria and was deemed suitable for physics instruction. Student trials revealed very good for both content and media aspects. Thus, the gamified genially based FISIPOLY proves feasible for enhancing physics education.